Sociodemographic and behavioural correlates of severe dental fluorosis - F. WONDWOSSEN, A. N. ÅSTRØM, K. BJORVATN,& A. BÅRDSEN (Paediatric Dentistry, 2006)
Dental fluorosis is caused by excessive intake of fluoride during the period of enamel formation, which occurs roughly during the first 10 years of life [1–4]. At the time of tooth eruption, fluorotic enamel exhibits a continuum of clinical features ranging from white opaque lines to entirely chalky white enamel [2,5,6]. The milder degrees of severity may regress as a result of enamel abrasion [3,6–8] or continuous mineralization [6–9].